Complement component C3 and C5b‐9 deposition on hypoxia reperfused endothelial cells by non‐HLA antibodies against RhoGDI2: A player involved in graft failure?. (1st November 2022) - Kardol‐Hoefnagel, Tineke; Michielsen, Laura A.; Ehlers, Anna M.; van Zuilen, Arjan D.; Luijk, Bart; Otten, Henny G.
Abstract : Antibodies against Rho GDP‐dissociation inhibitor 2 (RhoGDI2) are associated with inferior graft survival in transplant patients receiving a kidney from deceased donors. Although this suggests that these antibodies contribute to graft injury because of ischemia, it remains unknown whether they are also pathogenically involved in the process of graft loss. To study this, we firstly analyzed the IgG subclass profile of anti‐RhoGDI2 antibodies in kidney transplant recipients, and whether antibody titers change over time or because of acute rejection. Next, we investigated the expression of RhoGDI2 on primary kidney and lung endothelial cells (ECs) upon hypoxia reperfusion. In addition, the complement‐fixing properties of anti‐RhoGDI2 antibodies were studied using imaging flow cytometry. Anti‐RhoGDI2 antibodies in patients are mainly IgG1, and titers remained stable and seemed not be changed because of rejection. Antibodies against RhoGDI2, which surface expression seemed to increase upon hypoxia reperfusion, co‐localized with C3 on ECs. Binding of human IgG1 monoclonal anti‐RhoGDI2 antibodies as well as patient derived antibodies, resulted in complement activation, suggesting that these antibodies are complement fixing. This study suggested a potential pathogenic role of anti‐RhoGDI2 antibodies in kidney graft loss. During ischemia reperfusion, the ability of these antibodies to fix complement could be one of the mechanisms resulting in tissue injury.